2016
DOI: 10.3389/fphys.2016.00580
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant Peroxiredoxin 6 (Prdx6) Exhibits Different Profiles in the Livers of Seawater- and Fresh Water-Acclimated Milkfish, Chanos chanos, upon Hypothermal Challenge

Abstract: A tropical species, the euryhaline milkfish (Chanos chanos), is a crucial economic species in Southeast Asia and is intolerant of water temperature below 12°C. Large numbers of milkfish die during cold periods in winter. Hypothermal environments usually increase oxidative stress in teleosts, and the liver is the major organ for anti-oxidative responses in the body. Peroxiredoxin-6 (Prdx6) in mammals is a multi-functional enzyme and acts as both glutathione peroxidase, phospholipase A2 and acyl-transferase for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Additionally, our study demonstrated that PRDX6 level was significantly lower in CSC-exosomes, however, the catalase level was observed to be high. The role of PRDX6 as an antioxidant is known to suppress lipid oxidation and therefore PRDX6 helps in rescuing cellular toxicity from external agents 57 59 . Perhaps, it is possible that increased CYP1A1 expression and decreased PRDX6 level in exosomes could increase oxidative stress and resultant DNA damage and cellular toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our study demonstrated that PRDX6 level was significantly lower in CSC-exosomes, however, the catalase level was observed to be high. The role of PRDX6 as an antioxidant is known to suppress lipid oxidation and therefore PRDX6 helps in rescuing cellular toxicity from external agents 57 59 . Perhaps, it is possible that increased CYP1A1 expression and decreased PRDX6 level in exosomes could increase oxidative stress and resultant DNA damage and cellular toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the antioxidant system works depending on production of NADPH from the pentose phosphate pathway. Under hypothermal adaptation, FW milkfish encounter more oxidative stress in the liver than that by SW milkfish (Chang et al, 2016a , b , 2017 ). Therefore, the response of milkfish upon hypothermal and salinity stress may be correlated with the elevation of energy requirements.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of the immunoreactive band of the internal control in the immunoblot was set to one and used as a standard for normalizing relative intensities of other bands in the immunoblots. Relative abundance of target proteins was calculated using the following formula (TnFXYD8 n /actin n )/(TnFXYD8 internal control /actin internal control ) (Chang et al, 2016a , b ).…”
Section: Methodsmentioning
confidence: 99%
“…The methods used in this study to prepare renal crude membrane fractions were modified from our previous studies (Chang et al, 2016a ; Hu et al, 2017 ). After homogenization and centrifugation, the supernatants were collected and used to determine protein concentration or to do IP.…”
Section: Methodsmentioning
confidence: 99%